UPAYA PEMERINTAH DAERAH KAMPAR DALAM MEWUJUDKAN PRIORITAS PEMBANGUNAN DI BIDANG PERTANIAN TAHUN 2012-2013 - Hidayat, Taufiq; ", Muchid (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The background of the problem in this research is the Kampar seen from the geographical conditions has the potential land for agricultural development, it should Kampar own grand design development of the agricultural sector. Grand design is expected to encourage the development of Kampar regency which has the potential of wetland and upland area is promising, Kampar district has vast potential wetland rice fields where the vast potential in the Kampar area of 10 467 hectares. Potential dry land far greater extent than the existing wetland. Extensive dry land in Kampar regency is 197 346 ha. As an agricultural area that has the potential wetland and upland wide enough, either already or not yet in use, Kampar continually strive to cover the various needs of the community. Which became the focus of the problem in this research is how the Kampar District Government efforts to realize the development priorities in agriculture 2012-2013? and what factors inhibiting realize Kampar District Government development priorities in agriculture 2012-2013?. This type of research is a field research with qualitative approach. Pliers data collection techniques used were interviews primary data, in addition to observation and documentation as secondary data. The territories in which the research is Kampar and Stakeholders Department of Agriculture. The research findings indicate (1) upanya Kampar District Government Delivering On Agriculture Sector Development Priorities 2012-2013 through; Food Resilience improvement program, Program Increased production of agricultural / plantation, Program Improvement production of agricultural / plantation, Farmers Welfare Improvement Program, a program peningkatakn Marketing Results, programÂ¬progam have been realized by the local government through the agriculture office Kampar Kampar, this program has been successfully implemented physical and non-physical, physical has been accomplished 100%, but non-physical claim on average this program has accomplished 75% .. (2). Factors resistor Regency of Kampar implement Priority Development in Agriculture, the natural resources are not a constraint in building in Kampar because each district has resources sufficient to manage menjai agricultural land, but that the limiting factor is the human resources and support facilities to boost agriculture in Kampar, for human resources in the field of agriculture is the generation of tau are not many young people are engaged in agriculture, while it supported agriculture seeds and fertilizer aid and the government sometimes often has been delayed until at the hands of the farmers.Keyword: Government Kampar, Agriculture, production, resource